THE DEVELOPMENT OF SCIENCE IN THE USA AND ITS IMPACT ON THE ECONOMY IN THE SECOND HALF OF THE XX CENTURY (American Journal of Research in Humanities and Social Sciences, 2023)
This article discusses the development of science in the United States in the second half of the 20th century and its impact on the economy. Based on historical data, the author studied and analyzed specific aspects of the development of science in the USA in the second half of the 20th century and its impact on the economy based on available scientific literature.